Exploring technology acceptance and user behavior in Indonesia’s village fund system - Fuad, Khoirul; Ady Pamungkas, Septian Satria; Ahmad Nadzri, Farah Aida; Tajul Urus, Sharina (Universiti Teknologi MARA Selangor, 2025)
In Indonesia, advances in information technology particularly computer-based systems play a vital role in enhancing operational efficiency and effectiveness, including in village financial management. The Village Fund System (Sistem Keuangan Desa, or Siskeudes) has emerged as a key solution in promoting automation, transparency, and accountability in this process. This study aims to examine the factors influencing user behaviour in operating the Siskeudes application. Primary data were collected through questionnaires distributed to village officials directly involved in using Siskeudes, such as village heads, secretaries, treasurers, system operators, financial staff, and other relevant personnel. From a population of 20 villages, with five officials each, a total of 83 respondents were selected using purposive sampling. The data were analysed using SmartPLS version 3.0. The results show that Perceived Usefulness, Self-Efficacy, Computer Anxiety, and Computer Attitude have significant and positive effects on Siskeudes usage behaviour. However, Internal Locus of Control does not moderate these relationships.